Electrical properties and chemical stability of Br addition in BaCe0.8Gd0.2O3-α proton-conducting electrolyte. Issue 16 (November 2020) - Luo, Yadan; Li, Ying; Zhang, Ning; Ding, Yushi; Li, Hongzheng; Chen, Gang
Abstract: The effects of bromine (Br) addition on electrical properties and chemical stability of Gd-doped barium cerate proton-conducting electrolyte were investigated. BaCe0.8 Gd0.2 O2.8±δ Br0.2 (BCGBr) and BaCe0.8 Gd0.2 O3-α (BCG) powders with CuO as sintering aid were obtained via a solid-state reaction. The results of X-ray fluorescence (XRF) confirm that only trace amounts of Br are present in BCGBr after high temperature sintering at 1600 °C, indicating that Br addition influences stoichiometry but not directly the physicochemical properties. Nevertheless, the XRD results from the treated BCGBr and BCG electrolyte pellets show that the chemical stability of BCGBr in water and/or CO2 -containing atmospheres is conspicuously improved. The conductivities of electrolyte sintered at 1600 °C for 10 h were investigated in various atmospheres by AC impedance technique. The total conductivity ( σ t o t ) of BCGBr under wet Ar is lower than that of BCG. Partial-conductivities components ((proton ( σ OH O · ), oxygen ion ( σ V O · · ), and hole ( σ h · )) are presented for BCGBr according to the defect structure model. The results show that the proton conductivity of BCGBr remains nearly constant over the 550–750 °C temperature range. Although σ t o t of Br-synthesized sample slightly decreases, the BCGBr exhibits a high σ OH O · (0.058 S cm −1 at 750 °C) under pH2 O = 0.038 atm and pO2  = 1 atm. P-type and oxygen ion conduction are dominant in an oxidative atmosphere (pO2  = 1 atm) at 650 °C. Under low oxygen conditions (pO2  = 10 −4  atm), BCGBr shows the behavior of mixed conduction (oxygen ions ( V O · · ) and protons ( OH O · )). Besides, the main carriers in BCGBr oxide change from OH O · to V O · · as temperature increased.